Current Findings Regarding Natural Components With Potential Anti-2019-nCoV Activity - Zhou, Jin; Huang, Jie (Frontiers in Cell and Developmental Biology, 2020)
COVID-19, a novel coronavirus pneumonia (named by the World Health Organization, WHO), has spread widely since the end of 2019. Research on synthetic drugs and vaccines has become a focus of attention in China and other countries, as such approaches are regarded as key tools for disease prevention and control; however, the development of these therapeutics will take months, or even years. Under such circumstances, development of coronavirus speciﬁc therapeutics is urgent. For this specific indication, the rapid performance of natural products, such as plant compounds, herbal extracts, and traditional Chinese medicine, could contribute as alternative measures. Recent investigations have provided evidence that these natural products are potential candidates for development as therapeutic agents against the virus that causes COVID-19, 2019-nCoV. Targeting the structural proteins or cellular receptors of 2019-nCoV, including coronavirus chymotrypsin-like (3CLpro or Mpro), helicase (nsP13), S protein, and human angiotensin converting enzyme 2 (ACE2), holds promise for preventing infection. In this review, we summarize some representative natural products and their active components that have potential anti-2019-nCoV effects. We focus on the basic structural elements of 2019-nCoV, its main mechanisms of action, and the feasibility and potential of products to inhibit the novel coronavirus. In addition, the relative advantages, additional functions, and precautions that should be used with typical natural products are also discussed. The aim is to make the case that natural products could be a valuable pool for the development of active compounds for treating 2019-nCoV infection, which may contribute to mitigation of the spread of the pandemic.